CHN1 is a Novel Prognostic Marker for Diffuse Large B-Cell Lymphoma - Sun J; Zhu X; Zhao Y; Zhou Q; Qi R; Liu H (Dove Medical Press, 2021)
Jie Sun,1,2 Xiaoquan Zhu,3 Yanyang Zhao,3 Qi Zhou,3 Ruomei Qi,3 Hui Liu1,2 1Department of Hematology, Beijing Hospital, National Center of Gerontology, Institute of Geriatric Medicine, Chinese Academy of Medical Sciences, Beijing, People’s Republic of China; 2Graduate School of Peking Union Medical College, Chinese Academy of Medical Sciences, Beijing, People’s Republic of China; 3The Key Laboratory of Geriatrics, Beijing Hospital, National Center of Gerontology, Institute of Geriatric Medicine, Chinese Academy of Medical Sciences, Beijing, People’s Republic of ChinaCorrespondence: Hui LiuDepartment of Hematology, Beijing Hospital, National Center of Gerontology, Institute of Geriatric Medicine, Chinese Academy of Medical Sciences, No. 1 Dahua Road, Dongcheng District, Beijing, 100730, People’s Republic of ChinaEmail liuhui8140@126.comPurpose: Diffuse large B-cell lymphoma (DLBCL) is the most common B-cell malignancy. Thirty to forty percent of DLBCL patients still experience relapse or develop refractory disease even with standard immunochemotherapy, leading to a poor prognosis. Currently, although several gene-based classification methods can be used to predict the prognosis of DLBCL, some patients are still unable to be classified. This study was performed to identify a novel prognostic biomarker for DLBCL.Patients and Methods: A total of 1850 B-cell non-Hodgkin lymphoma (B-NHL) patients in 8 independent datasets with microarray gene expression profiles were retrieved from the Gene Expression Omnibus (GEO) database and Lymphoma/Leukemia Molecular Profiling Project (LLMPP). The candidate genes were selected through three filters in a strict pipeline. Survival analysis was performed in two independent datasets of patients with both gene expression data and clinical information. Gene set enrichment analysis (GSEA) and the CIBERSORT algorithm were used to explore the biological functions of the genes.Results: We identified 6 candidate genes associated with the clinical outcome of DLBCL patients: CHN1, CD3D, CLU, ICOS, KLRB1 and LAT. Unlike the other five genes, CHN1 has not been previously reported to be implicated in lymphoma. We also observed that CHN1 had prognostic significance in important clinical subgroups; in particular, high CHN1 expression was significantly related to good outcomes in DLBCL patients with the germinal center B-cell-like (GCB) subtype, stage III–IV, or an International Prognostic Index (IPI) score > 2. Multivariate Cox regression analysis of the two datasets showed that CHN1 was an independent prognostic factor for DLBCL. Additionally, GSEA and CIBERSORT indicated that CHN1 was correlated with cell adhesion and T cell immune infiltration.Conclusion: Our data indicate for the first time that high CHN1 expression is associated with favorable outcomes in DLBCL patients, suggesting its potential utility as a prognostic marker in DLBCL.Keywords: CHN1, diffuse large B-cell lymphoma, prognosis, biomarker